Antioxidant ability of potato (Solanum tuberosum) peel extracts to inhibit soybean oil oxidation. Issue 12 (18th May 2016) - Franco, Daniel; Pateiro, Mirian; Rodríguez Amado, Isabel; López Pedrouso, María; Zapata, Carlos; Vázquez, José Antonio; Lorenzo, José Manuel
Abstract : Potato peels are an agro industrial waste of one of the major crops worldwide. However, the potential of potato peels as source of antioxidants in the food industry is not yet sufficiently known. In this work, the antioxidant effect of potato peel extract (PPE) on oxidative stability of soybean oil was evaluated. We found that the addition of low PPE concentrations to soybean oil at four different levels, expressed as chlorogenic acid concentrations (14.01, 20.37, and 31.94 ppm), affected lipid oxidation indices (peroxide, anisidine, and conjugated dienes values), fatty acid composition, and volatile compounds. Antioxidant effect increased with increasing dose extract. Inhibition percentages of hexanal production increased with the PPE concentration. In addition, low concentrations of PPE showed higher oxidation stability than control untreated samples. Overall, our study shows that low concentrations of PPE exhibited promising antioxidant activity to be applied over a wider range of products in the food industry. Practical applications: The prevention of lipid oxidation during processing and storage of food products is of great concern in order to obtain products of high quality and health. Together with the fact that synthetic antioxidants may constitute a potential health hazard for consumers, interest in natural antioxidants and search on naturally occurring compounds with antioxidant activity has increased dramatically. The study of the antioxidant capacity of potato peel extracts to inhibit soybean oil oxidation provides information about an alternative antioxidant further are by‐products of agro‐industries and their use could represent a significant step toward maintaining an environmental balance. The prevention of lipid oxidation during processing and storage of food products is of great concern in order to obtain products of high quality and health. Together with the fact that synthetic antioxidants may constitute a potential health hazard for consumers, interest in natural antioxidants and search on naturally occurring compounds with antioxidant activity has increased dramatically. The study of the antioxidant capacity of potato peel extracts to inhibit soybean oil oxidation provides information about an alternative antioxidant further are by‐products of agro‐industries and their use could represent a significant step toward maintaining an environmental balance. Abstract : The prevention of lipid oxidation during processing and storage of food products is of great concern in order to obtain products of high quality and health. Together with the fact that synthetic antioxidants may constitute a potential health hazard for consumers, interest in natural antioxidants and search on naturally occurring compounds with antioxidant activity has increased dramatically. The study of the antioxidant capacity of potato peel extracts to inhibit soybean oil oxidation provides information about an alternative antioxidant further are by‐products of agro‐industries and their use could represent a significant step toward maintaining an environmental balance.